Predictive modeling for healthcare worker well-being with cloud computing and machine learning for stress management - Sudha, Muthukathan Rajendran; Malini, Gnanamuthu Bai Hema; Sankar, Rangasamy; Mythily, Murugaaboopathy; Kumaresh, Piskala Sathiyamurthy; Varadarajan, Mageshkumar Naarayanasamy; Sujatha, Shanmugam (Institute of Advanced Engineering and Science, 2025)
This paper provides a new method for stress management-focused predictive modeling of healthcare workers' well-being via cloud computing and machine learning. The need for proactive measures to track and assist healthcare workers' mental health is highlighted by the rising expectations placed on them. Using various data sources, our system compiles information from surveys, social media, electronic health records, and wearable devices into a single location for analysis. Predictive models that predict healthcare workers' stress levels and well-being are developed using gradient boosting, a strong machine learning (ML) technique. This work is suitable for gradient boosting due to its resilience to overfitting and capacity to process many kinds of data. Healthcare organizations may improve the health of their employees by using our technology to detect stress patterns and identify the causes of that stress. It can use specific treatments and support systems to alleviate that stress. Widespread adoption and real-time monitoring are made possible by the scalability, flexibility, and accessibility of cloud computing infrastructure. This method shows promise in the direction of proactive solutions driven by data for controlling the stress of healthcare workers and improving their general well-being.